The impact of cash social benefits for reducing poverty in the European Union - Balvočiūtė, Rasa (Socialinė teorija, empirija, politika ir praktika, 2019)
[full article and abstract in Lithuanian; abstract in English]This article presents an analysis of the impact of cash social benefits on poverty reduction in two groups of EU countries (The “Old,” Western Europe and the “New,” Eastern Europe ). Models of a regression analysis of panel data were compiled to assess the changes in the most deprived part of the population, which included factors such as population income, social assistance payments, labor market activity, population indebtedness, long-term unemployment and education levels of the population. The results of the survey revealed the essential differences in the impact of social assistance on poverty: in the old EU countries, means-tested social benefits reduce the growth of poverty and material deprivation; in the Eastern European countries, which are characterized by a more liberal or “residual” welfare model, the poorest part of the population changes due to cyclical fluctuations in economic development and changes in long-term unemployment. Therefore, the key for reducing poverty is to reduce long-term unemployment. Means-tested social benefits in them are as effective as in the old EU countries.
Keywords: cash social benefits; means-tested; monetary poverty; material deprivation; long-term unemployment